2021
DOI: 10.1515/cog-2020-0016
|View full text |Cite
|
Sign up to set email alerts
|

Using structural priming to test links between constructions: English caused-motion and resultative sentences inhibit each other

Abstract: Cognitive-linguistic theories commonly model speakers’ grammatical knowledge as a network of constructions related by a variety of associative links. The present study proposes that structural priming can provide psycholinguistic evidence of such links, and crucially, that the method can be extended to non-alternating constructions (i.e., constructions that differ in both form and meaning). In a comprehension priming experiment using the “maze” variant of self-paced reading, English caused-motion sentences wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…between benefactive and dative sentences; Ziegler & Snedeker 2018). As a result, priming effects are regarded as one of the strongest sources of evidence for the network model (Diessel 2019: 204;Ungerer 2021Ungerer , 2022.…”
Section: The Network Model: Characteristics and Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…between benefactive and dative sentences; Ziegler & Snedeker 2018). As a result, priming effects are regarded as one of the strongest sources of evidence for the network model (Diessel 2019: 204;Ungerer 2021Ungerer , 2022.…”
Section: The Network Model: Characteristics and Applicationsmentioning
confidence: 99%
“…priming) and the time course of language acquisition, but that there is no evidence that speakers store a separate schema for each group of similar constructions. In contrast to this position, Ungerer (2021Ungerer ( , 2022 suggests that priming effects can be equally interpreted as evidence for horizontal links and vertically related schemas, especially if it assumed that both links and schemas can vary in "strength", i.e. in their degree of entrenchment (Hilpert 2015;Langacker 2017; see also Schmid [2020: 234] for a gradient concept of the "likelihood of schematic representations").…”
Section: Types Of Network Linksmentioning
confidence: 99%
See 1 more Smart Citation
“…Boyce et al (2020) introduced several implementational innovations that made it easier for researchers to use Maze, and showed that for several controlled syntactic processing contrasts (Witzel et al, 2012) Maze offers better statistical power than self-paced reading, the other word-by-word response time method easy to use remotely. Maze has since had rapid uptake in the language processing community (Chacón et al, 2021;Levinson, 2022;Lieburg et al, 2022;Orth & Yoshida, 2022;Ungerer, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Boyce, Futrell, and Levy (2020) introduced several implementational innovations that made it easier for researchers to use Maze, and showed that for several controlled syntactic processing contrasts (Witzel, Witzel, and Forster 2012) Maze offers better statistical power than self-paced reading, the other word-by-word response time method easy to use remotely. Maze has since had rapid uptake in the language processing com-1 munity (Chacón et al 2021;Ungerer 2021;Orth and Yoshida 2022;Lieburg, Hartsuiker, and Bernolet 2022;Levinson 2022). However, there is increasing interest in collecting data during comprehension of more naturalistic materials such as stories and news articles (Demberg and Keller 2008;Luke and Christianson 2016;Futrell et al 2020), which offer potentially improved ecological validity and larger scale data in comparison with repeated presentation of isolated sentences out of context.…”
Section: Introductionmentioning
confidence: 99%